2018
DOI: 10.1016/j.mex.2018.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of bioaerosol particle characteristics at different hospital wards and operating theaters: A case study in Tehran

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 47 publications
(90 reference statements)
3
16
0
Order By: Relevance
“…We found lower concentrations of fungi than bacteria in all samples. Consistent with our results Mousavi et al (2019) and Bolookat et al reported the higher level of bacteria in hospitals bioaerosols samples [ 9 , 24 ].…”
Section: Discussionsupporting
confidence: 93%
“…We found lower concentrations of fungi than bacteria in all samples. Consistent with our results Mousavi et al (2019) and Bolookat et al reported the higher level of bacteria in hospitals bioaerosols samples [ 9 , 24 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our results indicated that heterotrophic bacteria were the most abundant microorganisms in the air of the investigated pharmacies. Similar results were obtained by Bolookat et al (2018) investigating hospital in Tehran: the average concentration of bacteria (919 CFU m -2 ) was higher than the average concentration of molds (796 CFU m -2 ). The highest average concentration of heterotrophic bacteria was recorded in summer (1054 CFU m -3 ) and the lowest, in winter (509 CFU m -3 ).…”
Section: Bacterial Bioaresol Concentrationsupporting
confidence: 86%
“…In other studies Aspergillus spp. were the most common molds isolated from the hospital environment, constituting 49.9% (Bolookat, et al 2018) and 47% (Cho et al 2018) of all molds.…”
Section: Concentration and Identification Of Moldsmentioning
confidence: 99%
“…Our study demonstrated that fungal bioaerosol concentrations were higher in the inpatient facilities of hospitals compared to the restricted and public areas. The increased fungal bioaerosol concentrations is likely due to the increased bed numbers used in inpatient facilities [40] such as those facilities which accommodate patients in multi-bed rooms. Despite the total fungal bioaerosol concentrations being higher in the inpatient…”
Section: Discussionmentioning
confidence: 99%